A ascensão da lógica financeira sob a perspectiva da teoria do capitalismo acadêmico: consequências para a formação do engenheiro de produção - Sigahi, Tiago Fonseca Albuquerque Cavalcanti (2017)
This research explores the ways through which a network of actors inside (e.g. administrators, professors, students, departments) and outside (e.g. governments, corporations, multilateral organizations, private foundations) university – including the university itself – engages in the process of blurring the boundaries between public and private, a phenomenon known as academic capitalism. This study articulates research on organization theory, higher education and sociology of economy, and employs theoretical (systematic literature review, narrative literature research and document analysis) and empirical (questionnaires, case study, business press, social networks, interviews) approaches. Initially, an overview on Theory of Academic Capitalism' research is presented, comparing it with competing/complementary theories, and proposing classification schemes based on analytical level, research focus, and findings. In analyzing transformations of Brazilian higher education from macrostructural/organizational perspectives, it will be argued that academic capitalism takes its first steps after the Reform of 1968; rises and gains more intense contours in the 80's; consolidates in the 90's; instrumentalizes itself in the 2000s and based on the associations between the current government and the business sector, threatens to take an even more aggressive form in the coming years. This process has facilitated the entry of actors of the Finance field (banks, investment funds, gurus of management, CEOs-celebrity) into the field of higher education, who find in student organizations the meanings to reproduce narratives, discourses, behaviors, and performance metrics aligned with financial logic, legitimizing a new ethos and influencing student education. In the case of the production engineers' education, which is the focus of this work, such transformations can be perceived in the rapid expansion of the Financial Market Leagues (FML), a movement that gained projection only in 2015, but have already reached 56 Brazilian universities. A survey with 82 members of these organizations revealed that these students, influenced by the perception that such environments represent not only greater financial gains but also more challenging/dynamic opportunities, have increasingly fueled expectations of inclusion in the financial sector. A case study conducted in the undergraduate course of Production Engineering at a national public university (NPU) allowed to verify an increase of 450% in the annual average of internships in this sector after the creation of the FML on this campus, in addition to the decrease (33%) of graduates in the industrial sector. On the one hand, the FML-NPU fostered a dynamics that strengthened the ties between university and financial sector actors, boosting the insertion of students in this sector. On the other hand, it triggered a sociocultural dynamic that sometimes subtly, sometimes explicitly, hierarchizes the students between "the selected and the unselected", between those who "went to the bank" and those who did not, segregating them. Interviews with the founders of FML-NPU revealed the strategies used to co-opt "easy-to-shape" students, catechizing them according to the aggressive culture of results. It will be sought to demonstrate that the data presented here represent to some degree one of the consequences of the rise of the aforementioned financial logic, firstly announced in the productive sphere and now sneaks into the education of production engineers itself.